2020
DOI: 10.3349/ymj.2020.61.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Profile: Firefighter Research on the Enhancement of Safety and Health (FRESH), a Prospective Cohort Study on Korean Firefighters

Abstract: Firefighters have a high risk of developing cardiovascular and mental disorders due to their physical and chemical environments. However, in Korea, few studies have been conducted on environmental risk of firefighters. The Firefighter Research on the Enhancement of Safety and Health (FRESH) study aimed to discover the risk factors for cardiovascular disease and mental disorders among firefighters. Former and current firefighters were recruited from three university hospitals. A total of 1022 participants compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…The prevalence rate of poor sleep quality ranges from 52.45% to 86.8% in Korean firefighters. 17 35 36 37 Our study showed that the poor sleep quality group was 59.3%. The result of this study was also similar to those of the poor sleep quality group compared to previous studies in Korea.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The prevalence rate of poor sleep quality ranges from 52.45% to 86.8% in Korean firefighters. 17 35 36 37 Our study showed that the poor sleep quality group was 59.3%. The result of this study was also similar to those of the poor sleep quality group compared to previous studies in Korea.…”
Section: Discussionmentioning
confidence: 64%
“…In the cohort of firefighters, the average BMI was 24.83 which was not significantly different from this panel composition. 37 In addition, a few studies showed that the sleep problem contributed to weight gain in middle-aged women and men, but it was significant only in women and not in men. 50 Also, in a study conducted in Korea, the association between sleep quality and obesity measured by PSQI was related in women, but not in men.…”
Section: Discussionmentioning
confidence: 99%
“…Firefighters who had not received psychiatric treatment but complained of PTSD-related symptoms were recruited for voluntary participation. This study's participants were previously included in the Firefighter Research on the Enhancement of Safety and Health (FRESH) cohort 13 and had therefore been assessed for their physical and psychological health status. All participants completed the Korean version of the Posttraumatic Diagnostic Scale (PDS) for PTSD screening.…”
Section: Methodsmentioning
confidence: 99%
“…We recruited 1,022 participants from the Firefighter Research on Enhancement of Safety & Health (FRESH) cohort, 13 including firefighters and rescue workers, assessed at three university hospitals between 2016 and 2017: Severance Hospital recruited firefighters from Seoul, Gyeonggi, Chungcheongnam-do, Daejeon, and Jeollabuk-do regions; Wonju Severance Christian Hospital recruited firefighters from Gangwon and Chungcheongbuk-do regions; and Gyeongsang National University Hospital recruited firefighters from Gyeongsangbuk-do, Gyeongsangnam-do, and Jeollanam-do regions. To assess psychological characteristics, we conducted several self-reporting questionnaire.…”
Section: Methodsmentioning
confidence: 99%